Pengaruh Pemahaman Akuntansi Terhadap Implementasi SAK EMKM (Survei pada UMKM Kuliner di Kota Bandung) - R. Ait Novatiani; Diana Sari; Nuryaman; Bachtiar Asikin; Rita Yuniarti; Robertus Ary Novianto (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2023)
The purpose of this research is to analyze the effect of accounting understanding on the implementation of SAK EMKM. The population selected in this study is culinary SMEs in the city of Bandung. The sample in this study used convenience sampling technique in order to obtain as many as 60 culinary SMEs. In this study, a simple regression analysis method with SPSS 20 was used. The results of the study provide evidence that the better the understanding of accounting, the better the implementation of SAK EMKM.